2020
DOI: 10.1093/clinchem/hvaa091
|View full text |Cite
|
Sign up to set email alerts
|

Potential False-Negative Nucleic Acid Testing Results for Severe Acute Respiratory Syndrome Coronavirus 2 from Thermal Inactivation of Samples with Low Viral Loads

Abstract: recommended to inactivate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) before NAT. However, this procedure could theoretically disrupt nucleic acid integrity of this single-stranded RNA virus and cause false negatives in real-time polymerase chain reaction (RT-PCR) tests. METHODS:We investigated whether thermal inactivation could affect the results of viral NAT. We examined the effects of thermal inactivation on the quantitative RT-PCR results of SARS-CoV-2, particularly with regard to the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
237
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(252 citation statements)
references
References 18 publications
8
237
2
5
Order By: Relevance
“…In a retrospective analysis involving 161 COVID-19 patients, the authors showed that false-negative test results of SARS-CoV-2 viral RNA were mainly caused by poor-quality sampling and that swabs did not contain a sufficient quantity of cellular materials [ 72 ]. Furthermore, thermal inactivation also decreases the sensitivity of RT-PCR tests for SARS-CoV-2 [ 73 ].…”
Section: Potential Cause Of Re-detectable Positive Sars-cov-2 Virus Imentioning
confidence: 99%
“…In a retrospective analysis involving 161 COVID-19 patients, the authors showed that false-negative test results of SARS-CoV-2 viral RNA were mainly caused by poor-quality sampling and that swabs did not contain a sufficient quantity of cellular materials [ 72 ]. Furthermore, thermal inactivation also decreases the sensitivity of RT-PCR tests for SARS-CoV-2 [ 73 ].…”
Section: Potential Cause Of Re-detectable Positive Sars-cov-2 Virus Imentioning
confidence: 99%
“…20 This study demonstrated a rate of re-detectable positive nucleic acid as high as 52.7% (39/74) despite strict adherence to domestic guidelines on discharge criteria, which may be attributed to the fact that SARS-CoV-2 mainly resides in the lower respiratory system. 21,22 In addition, possible deviation in specimen collection may lead to false negativity of nucleic testing and consequently inappropriate discharge decisions, 23,24 resulting in recurrence and even deterioration of the disease. The 20 patients with re-detectable positive nucleic acid displayed decline in lymphocyte subsets on the second admission, which was similar to the changes of initial infection.…”
Section: The Association Of Sars-cov-2 Antibodies With Re-detectablementioning
confidence: 99%
“…(10,13) In mild disease, especially in the early stages, the RT-PCR false negative rate is ~30-40%. (8,14,15) A meta-analysis reported that a single test ~10 days post symptom development had a ~33% false negative rate using a nasopharyngeal swab (52.89% for a throat swab). (16) Ai et al reported a false negative rate of 41% in a cohort of 1014 hospitalised patients; the estimated median interval between the initial negative test and subsequent positive RT-PCR result was 5.1 ± 1.5 days.…”
Section: Clinical and Immunodiagnostic Trajectory Of Covid-19 And Sammentioning
confidence: 99%
“…(19) This false negativity phenomenon may be due to several factors, including a low viral load below the detection limit of the assay, low sample volume or cellular mass during acquisition, sampling location (upper versus lower respiratory tract), sample degradation during transport or storage, sample processing methodology and the timing of sampling in relation to the stage of the disease (RT-PCR positivity may progressively increase during the course of the disease). (14) Test accuracy will depend on the quality of the specimen collected. (20) It has since been shown that specimens from the lower respiratory tract have a higher viral load and hence more likely to test positive than specimens from the upper respiratory tract.…”
Section: Clinical and Immunodiagnostic Trajectory Of Covid-19 And Sammentioning
confidence: 99%